Encyclopaedia of Bioinformatics - C Kuppuswamy (Dominant Publishers and Distributors, 2006)
The present publication in five volumes is an extensive work on Bioinformatics and covers much more of the subject as is generally expected of students going up for the examinations of several Universities in India and abroad. It has been written to present a logical and practical approach to the various complexities and intricacies of the subject at length. Almost every aspect of the subject is covered and illustrated by well labeled diagrams. In spite of the comprehensiveness, the subject matter has been presented in such a way that it is easily accessible to the students.